2020
DOI: 10.1186/s11671-020-03300-5
|View full text |Cite
|
Sign up to set email alerts
|

Nec-1 Attenuates Neurotoxicity Induced by Titanium Dioxide Nanomaterials on Sh-Sy5y Cells Through RIP1

Abstract: Titanium dioxide nanomaterials are applied in numerous fields due to their splendid physicochemical characteristics, which in turn poses a potential threat to human health. Recently, numerous in vivo studies have revealed that titanium dioxide nanoparticles (TNPs) can be transported into animal brains after exposure through various routes. Absorbed TNPs can accumulate in the brain and may disturb neuronal cells, leading to brain dysfunction. In vitro studies verified the neurotoxicity of TNPs. The mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…161 TiO 2 NPs were shown to cause endoplasmic reticulum (ER) stress, autophagy, inhibition of cell proliferation, disturbance of the microtubule dynamics, and membrane damage in SH-SY5Y cells. [153][154][155][156][157][158] Several in vivo studies investigated the neurotoxic effects of TiO 2 NPs on mouse hippocampus. However, one in vitro study explored the neurotoxic effects of TiO 2 NPs on mouse hippocampal neuronal HT22 cells.…”
Section: Neurotoxic Effects Of Tio 2 Nps In Vitro Modelsmentioning
confidence: 99%
“…161 TiO 2 NPs were shown to cause endoplasmic reticulum (ER) stress, autophagy, inhibition of cell proliferation, disturbance of the microtubule dynamics, and membrane damage in SH-SY5Y cells. [153][154][155][156][157][158] Several in vivo studies investigated the neurotoxic effects of TiO 2 NPs on mouse hippocampus. However, one in vitro study explored the neurotoxic effects of TiO 2 NPs on mouse hippocampal neuronal HT22 cells.…”
Section: Neurotoxic Effects Of Tio 2 Nps In Vitro Modelsmentioning
confidence: 99%
“…This may lead TiO 2 -NPs to be toxicologically potent than previously known. [52,[132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] ZnO-NPs…”
Section: Mgo-npsmentioning
confidence: 99%
“…Several in vivo and in vitro studies have demonstrated the neurotoxicity of TiO 2 NPs through programmed cell death processes, such as apoptosis, autophagy and necroptosis depending on the duration of exposure and the dose-dependence. Although low-dose exposure could not induce any acute neurotoxicity, chronic exposure to low dose TiO 2 NPs results in TiO 2 accumulation and might lead to dramatic changes in the brain [ 43 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Tio 2 Nps Hazard For Human Healthmentioning
confidence: 99%